A comparison of bone mineral densities and body composition between Southeast Asia college students and Chinese college students. Issue 37 (September 2016) - Liu, Peng; Ye, Ziliang; Lu, Jingjing; Lu, Haili; Guan, Liping; Teng, Zhihai; Gao, Shangzhi; Li, Mingyi
Abstract : Abstract: The aim of this study was to compare bone mineral densities (BMDs) and body composition between Southeast Asia college students and Chinese college students, in order to provide a certain reference enhancing college students' physical fitness. A total of 1694 Chinese college students (294 men and 1400 women, aged 18–22 years) and 250 Southeast Asia college students (148 men and 102 women, aged 19–22 years) were included in the study. Weight, height, and body mass index were measured anthropometrically. BMD values were determined by ultrasound bone densitometer and body composition was determined by body composition analyzer. Southeast Asia college students were overweight than Chinese college students (250 vs 1694) ( P < 0.05). Chinese college students had a significantly lower body weight, fat mass, lean tissue mass, lean body weight, estimation of bone mass, protein, and metabolic rate but higher BMD at the calcaneus compared with Southeast Asia college students ( P < 0.05 for all parameters). However, body water, intracellular fluid, and extracellular fluid were not significantly different between Chinese college students and Southeast Asia college students ( P > 0.01 for all parameters). The results of this cross-sectional study suggest that Chinese college students had a higher BMD but lower body composition than Southeast Asia college students, which may be associated with genes, diet, exercise, and other factors.